2005
DOI: 10.1016/j.seizure.2004.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Generator replacement in epilepsy patients treated with vagus nerve stimulation

Abstract: EOES or EOBL may be indicated by loss of seizure control, decreased or irregular perception of stimulation by the patient and loss of other VNS-induced effects. Postponing generator replacement may result into permanent loss of seizure control. In responders we suggest generator replacement before EOBL. Our results call for performance of prospective studies in larger patient groups that may eventually lead to general guidelines on the indication and timing of generator replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 17 publications
0
18
0
1
Order By: Relevance
“…There are several case reports describing outcomes of seizure patients who either (1) intentionally stop VNS or (2) have device malfunctions; or when (3) EOBL occurs. Vonck et al 7 reported 14/76 of their patients treated with VNS primarily for epilepsy experienced end of effective stimulation (EOES, end of service; wand identifies near EOBL) or frank EOBL. Seven of these patients also showed loss of seizure control (N=3), decreased perception of stimulation (N=3) and recurrence of depression (N=1).…”
Section: Discussionmentioning
confidence: 99%
“…There are several case reports describing outcomes of seizure patients who either (1) intentionally stop VNS or (2) have device malfunctions; or when (3) EOBL occurs. Vonck et al 7 reported 14/76 of their patients treated with VNS primarily for epilepsy experienced end of effective stimulation (EOES, end of service; wand identifies near EOBL) or frank EOBL. Seven of these patients also showed loss of seizure control (N=3), decreased perception of stimulation (N=3) and recurrence of depression (N=1).…”
Section: Discussionmentioning
confidence: 99%
“…(1) in 11 of their 18 cases, and by Vonck et al. (2) in 7 of their 14 cases. Whether VNS generators should be replaced before EOBL symptoms, or should be replaced at all (4), has been debated.…”
Section: Discussionmentioning
confidence: 80%
“…We were curious whether this might be related to an underlying change in neural function after chronic stimulation vs. other factors; and whether this had an impact on antiepileptic efficacy. In smaller previous series (1,2), this also had been noted, but details of the extent of this phenomenon were not studied specifically with a systematic postoperative device programming protocol employed. We reviewed our experience with VNS stimulation parameters after generator replacement.…”
Section: Introductionmentioning
confidence: 98%
“…This is particularly important in long-term follow-up, since patients tend to reduce the frequency of their visits once the parameters have been established, and often forget that the battery will eventually run out. Most currently used VNS models have batteries that last anywhere between four and 10 years -varying according to the energy spent -i.e., value of the output current, duty cycle and frequency of use of the magnet 23 .…”
Section: Recommendations For Vns Adjustment and Managementmentioning
confidence: 99%